Answer:
-12 - 51i
Step-by-step explanation:
[tex]original:(-6-3i)*(5+6i)\\FOIL:(-6)(5)+(-6)(6i)+(-3)(5)+(-3i)(6i)\\Multiply:(-30)+(-36i)+(-15i)+(18i^2)\\Combine\ Like\ Terms:(-30) + (-51i)+(-18i^2)\\i^2\ =\ -1:(-30)+(-51i)+(-18)(-1)\\Multiply:(-30)+(-51i)+(18)\\Combine\ Like\ Terms:(-12) + (-51i)\\Simplify:-12-51i[/tex]
Thing to remember:
[tex]i = \sqrt{-1} \\i^2 = \sqrt{-1}*\sqrt{-1} = \sqrt{-1}^2 = -1\\i^3 = \sqrt{-1}*\sqrt{-1}*\sqrt{-1} = i^2 * i = (-1)*i = -i\\i^4 = \sqrt{-1}*\sqrt{-1}*\sqrt{-1}*\sqrt{-1} = \sqrt{-1}^2*\sqrt{-1}^2 = (-1)*(-1) = 1\\[/tex]
And all powers over 4 repeat such that [tex]i^x\ such\ that\ x\mod4 = y[/tex] is the same as [tex]i^y\\[/tex]:
i.e.:
[tex]i^6 = i^{4+2}= i^4*i^2 = 1*-1 = -1\\\\i^9 = i^{4+4+1}=i^4*i^4*i^1=(1)(1)(i) = i[/tex]
NOTE: x mod 4 simply means the remainder when x is divided by 4.
i.e.:
[tex]7\mod4 = 3\\8\mod4 = 0\\13\mod4 = 1[/tex]